PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN SAHAM PADA PERUSAHAAN INDUSTRI SUBSEKTOR BARANG KONSUMSI PERIODE 2017-2020 - Lenny Lenny; Lamria Sagala; Tri Dharma Sipayung (JURNAL MANAJEMEN, 2022)
The purpose of this study is to examine and analyze the effect of Profitability, Leverage, Liquidity, And Sales Growth to Stock Returns of Consumer Goods Subsector Industrial for the period 2017-2020. The data used in this study are Secondary data consists of the annual financial statements and annual reports of industrial companies of the consumer goods subsector listed on the Indonesian stock exchange. The population in this study are 62 customer goods companies and which are met the criteria of being a study sample were 27 samples selected through the purposive sampling method. The independent variables in the study were Profitability, Leverage, Liquidity, And Sales Growth and the dependent variable is Stock Return. Methods of data analysis using descriptive statistical methods, classical assumption test, regeresis test, and hypothesis test show that Sales Growth partially have a positive and significant effect on Stock Return while Profitability, Leverage, and Liquidity partially have a positive but not significant effect on Stock Returns, as well as simultaneous profitability, leverage, Liquidity, And Sales Growth have a significant effect on Stock Returns.Â